Tanggung Jawab Hukum Rumah Sakit Terhadap Insiden Bayi Dipulangkan Pada Orang Tua Yang Salah - Krisnawati, Ristyani (PSHPM Untag Semarang, 2023)
The incident of a newborn being discharged to the wrong parents in a hospital can lead to legal issues that result in hospital liability. The incident is the negligence of health workers in the hospital in identifying newborns and is classified as a sentinel event, which is one type of patient safety incident. This article aims to find out how the hospital's legal responsibility for the negligence of health workers in providing health services to patients. Chapter 46 of Hospital Law Number 44 of 2009 concerning Hospitals regulates that hospitals must be legally responsible for all losses incurred by health workers in the hospital. The hospital in this case applies the doctrine of Corporate Liability. The application of the doctrine of Corporate Liability also requires hospitals to always supervise and control all forms of actions taken by their subordinates so that negligence does not occur which results in harm to patients. The form of hospital responsibility by compensating patients for negligence caused by health workers.